MAGNETIC TRANSITION AND SOUND VELOCITIES OF FE3S AT HIGH PRESSURE: IMPLICATIONS FOR EARTH AND PLANETARY CORES - Lin J.-F.; Fei Y.; Mao H.-K.; Hemley R.J.; Sturhahn W.; Zhao J. (My University, 2004)
Magnetic, elastic, thermodynamic, and vibrational properties of the most iron-rich sulfide, Fe3S, known to date have been studied with synchrotron Mossbauer spectroscopy (SMS) and nuclear resonant inelastic X-ray scattering (NRIXS) up to 57 GPa at room temperature. The magnetic hyperfine fields derived from the time spectra of the synchrotron Mossbauer spectroscopy show that the low-pressure magnetic phase displays two magnetic hyperfine field sites and that a magnetic collapse occurs at 21 GPa. The magnetic to non-magnetic transition significantly affects the elastic, thermodynamic, and vibrational properties of Fe3S. The magnetic collapse of Fe3S may also affect the phase relations in the iron–sulfur system, changing the solubility of sulfur in iron under higher pressures. Determination of the physical properties of the non-magnetic Fe3S phase is important for the interpretation of the amount and properties of sulfur present in the planetary cores. Sound velocities of Fe3S obtained from the measured partial phonon density of states (PDOS) for 57Fe incorporated in the alloy show that Fe3S has higher compressional and shear wave velocity than those of hcp-Fe and hcp-Fe0.92Ni0.08 alloy under high pressures, making sulfur a potential light element in the Earth's core based on geophysical arguments. The VP and VS of the non-magnetic Fe3S follow a Birch's law trend whereas the slopes decrease in the magnetic phase, indicating that the decrease of the magnetic moment significantly affects the sound velocities. If the Martian core is in the solid state containing 14.2 wt.% sulfur, it is likely that the non-magnetic Fe3 phase is a dominant component and that our measured sound velocities of Fe3S can be used to construct the corresponding velocity profile of the Martian core. It is also conceivable that Fe3P and Fe3C undergo similar magnetic phase transitions under high pressures.